Pengembangan Sistem Informasi Pembelian, Penjualan dan Persediaan Motor Bekas menggunakan Analisis Fast-Slow-Non Moving - Renaldy Renaldy; Teddy Marcus (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Abstract — Motorcycle Company is engaged in selling used motorcycles, processing motorcycle inventory data to manage the optimal number of purchases and sales. Based on monthly sales data, it can be predicted the need to buy a used vehicle to the seller. Through FSN (Fast-moving, Slow-moving and Non-moving) analysis is to consider quantity, the rate of consumption of item and how often they are issued or used. The results of analysis can be used to guide the decision of the right amount of inventory to be placed in the warehouse, the frequency to buy or even delete certain items in stages. In order for the FSN analysis to be carried out successfully, it is necessary to analyze the items based on their respective categories, within a certain period of time. The purpose of this research is to design and build an information system for the sale of used motor vehicles, purchase of used motorcycles by considering the optimal inventory using the FSN method. Keywords — Inventory Management, Selling-buying Used Motorcycle, Fast-moving, Slow-moving and Non-moving Anylysis.